The relationship between adaptive management of social-ecological systems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managing social-ecological systems involving high levels of complexity and uncertainty. However, many obstacles still hamper its implementation. Law is often seen as a barrier for moving adaptive management beyond theory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this knowledge gap by providing a systematic review of the peer-reviewed literature on the relationship between adaptive management and law in relation to social-ecological systems. We analyze how the scholarship defines the concept of adaptive management, identifies the legal barriers to adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geographically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our results show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Legal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation but also to make law itself more adaptive.

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.

Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (Complexity and Development Seminar Series, 2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.